Controlled synthesis and photocatalysis of sea urchin-like Fe3O4@TiO2@Ag nanocomposites. Issue 9 (17th February 2016) - Zhao, Yilin; Tao, Chengran; Xiao, Gang; Wei, Guipeng; Li, Linghui; Liu, Changxia; Su, Haijia
Abstract : Based on the synergistic photocatalytic activities of nano-sized TiO2 and Ag, as well as the magnetic properties of Fe3 O4, a sea urchin-like Fe3 O4 @TiO2 @Ag nanocomposite (Fe3 O4 @TiO2 @Ag NCs) is controllably synthesized with tunable cavity size, adjustable shell layer of TiO2 nanofiber, higher structural stability and larger specific surface area. Abstract : Based on the synergistic photocatalytic activities of nano-sized TiO2 and Ag, as well as the magnetic properties of Fe3 O4, a sea urchin-like Fe3 O4 @TiO2 @Ag nanocomposite (Fe3 O4 @TiO2 @Ag NCs) is controllably synthesized with tunable cavity size, adjustable shell layer of TiO2 nanofiber, higher structural stability and larger specific surface area. Here, Fe3 O4 @TiO2 @Ag NCs are obtained with Fe3 O4 as the core and nanofiber TiO2 /Fe3 O4 /Ag nanoheterojunctions as the shell; and Ag nanoparticles with diameter of approximately 4 nm are loaded both on TiO2 nanofibers and inside the cavities of sea urchin-like Fe3 O4 @TiO2 nanocomposites uniformly. Ag nanoparticles lead to the production of more photogenerated charges in the TiO2 /Fe3 O4 /Ag heterojunction via LSPR absorption, and enhance the band-gap absorption of TiO2, while the Fe3 O4 cocatalyst provides the active sites for oxygen reduction by the effective transfer of photogenerated electrons to oxygen. So the photocatalytic performance is improved due to the synergistic effect of TiO2 /Fe3 O4 /Ag nanoheterojunctions. As photocatalysts under UV and visible irradiation, the as-synthesized nanocomposites display enhanced photocatalytic and recycling properties for the degradation of ampicillin. Moreover, they present better broad-spectrum antibiosis under visible irradiation. The enhanced photocatalytic activity and excellent chemical stability, in combination with the magnetic recyclability, makes this multifunctional nanostructure a promising candidate for antibiosis and remediation in aquatic environmental contamination in the future.